Introduction of 'patient safety' module to undergraduate medical students through an interactive workshop - Roopam Kumar R. Gupta (Journal of Clinical and Scientific Research, 2023)
Background: The World Health Organization (WHO) had developed a curriculum guide designed to shape foundation knowledge and skills of medical students to sensitise them regarding 'Patient Safety'. 'Patient Safety' is not emphasised in the current undergraduate (UG) medical curriculum. This study is an attempt to know the effectiveness of introducing a 'Patient Safety' Module based on the WHO's proposed curriculum, through an interactive workshop for UG medical students. Methods: This cross-sectional study was conducted with 77 students of 2nd year Bachelor of Medicine, Bachelor of Surgery (MBBS). Three topics of the WHO's 'Patient Safety Curriculum' were taught through an 'Interactive workshop' and a study tool, comprising of multiple-choice question and Likert scale. A questionnaire was also administered pre- and post-workshop, followed by a 'field activity' which allowed students to apply their newly learnt knowledge in a real hospital setting. Feedback was taken and qualitatively analysed. Results: The mean score of first section of the study tool was 9.2 (45.9%) in pre-test and 14.6 (73.2%) in post-test, with a positive difference of 5.5 (27.4%) marks. The analysis of section 2 showed a significant positive change in the knowledge level, but a non-significant change was noted for the level of agreement, own ability to influence, personal attitudes with regard to patient safety and expectations about patient care. Overall analysis of the second section revealed a significant change to the positive side. Conclusions: 'Interactive Workshop' significantly increased the knowledge regarding patient safety, and therefore, it is an effective method to teach 'patient Safety' to UG medical students.